Let’s all be good! - Tobin, William (New Zealand Science Review, 2012)
​Over the years the idea has been gaining ground that science and technology are the essential foundation on which to build a more prosperous and ecological New Zealand. A usual con-comitant view is that in a time of tight money, only the most excellent science should receive government support. A panoply of administrative measures have been devised to this end, such as highly-competitive Marsden Fund research contracts and the Quality Evaluation of the Performance Based Research Fund (PBRF).